Dreamland's: know about science magnetism - Talwar, L.M (Dreamland Publications New Delhi, 1995)
Dreamland's: Know About Science - Magnetism dives into the fascinating world of magnets. It covers essential concepts like magnetic forces, the properties of magnets, and how they interact with various materials. With interactive elements and experiments, the book helps children understand magnetism in a practical and engaging way.